UMP thesis management system - Mohammad Thalhah Amir, Abdul Rahman (2011)
University Malaysia Pahang Online Thesis Management Systems (lJMPthesis) is a web management system that uses as thesis management that functioning as storing data,read thesis, marking the thesis,comment on thesis,and so on.The idea to build the system by using web management systems is because nowadays internet has widely used and already become a lifestyle.Besides,UMP has wide coverage of internet where all campus area has internet coverage so students and lecturer can online the systems anywhere,anytime in the campus with free of charges.In order to build the system, the plan is by using Software Development Life Cycles (SDLC).SDLC has five stages that are planning, analysis, design,implementation and maintenance.The system use PUP and html language.As medium to store data,MySQL will be used. As a result,the systems will work nicely and will help staff to organize thesis and easier for students to make references.